2021
DOI: 10.1177/20584601211028994
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of pain reduction after vertebroplasty and kyphoplasty

Abstract: Background Various studies have been made about the most effective and safest type of treatment for vertebral compression fractures (VCFs). Long-term results are needed for qualitative evaluation. Purpose The purpose of the study is to evaluate the effectiveness of percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP) procedures for VCFs. Materials and Methods Forty-nine patients who received either PVP or PKP between 2002 and 2015 returned a specially developed questionnaire and were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We assessed how well the treatment's effects were examined on osteoporotic VCFs. We showed that PVP and PKP considerably reduce pain in patients with VCFs by evaluating the data gathered to evaluate patient outcomes [12]. Our analysis included patient data from interventional treatment administered between January and December of 2020, with an average one-year gap between treatment and clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed how well the treatment's effects were examined on osteoporotic VCFs. We showed that PVP and PKP considerably reduce pain in patients with VCFs by evaluating the data gathered to evaluate patient outcomes [12]. Our analysis included patient data from interventional treatment administered between January and December of 2020, with an average one-year gap between treatment and clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The visual analogue scale (VAS score 0-10; 0 no pain at all; 10 the worst imaginable) system was employed to evaluate back pain control. Impact on the patient's daily life was assessed using the Oswestry Disability Index (ODI) questionnaire [11,12]. Radiographs were taken to measure the rate of cement leakages and refracture, the anterior, middle and posterior vertebral heights, Cobb's angle and Vertebral wedge ratio [11] of the fractured vertebral body before and after surgery.…”
Section: Clinical and Radiologic Assessmentmentioning
confidence: 99%
“…The majority of OVCF patients mainly showed the loss of anterior vertebral height and the increase of kyphotic angle on X-ray lateral lms, while OVOCF patients showed the serious loss of vertebral height and the increase of vertebral scoliosis angle on X-ray lateral lms. Both bone cement and bone cement combined with balloon have achieved signi cant clinical e cacy in the treatment of OCVF induced spinal pain, and their main roles are to restore vertebral height and strength, correct kyphosis, and rebuild spinal stability 22,23 . In the past, when they were used to treat OVCF, only the sagittal height of vertebral body was restored, and kyphosis was corrected 24 .…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 41 , 70 , 71 However, recent data on the impact of kyphoplasty or vertebroplasty on HRQOL are limited, and vertebroplasty is controversial, as studies on its efficacy in reducing mCIBP are mixed. 72–75 A 2021 publication reported that, in patients with cancer pain due to bone metastases, pain was significantly reduced and HRQOL was significantly improved up to 6 months after either radiofrequency ablation alone or radiofrequency ablation with vertebroplasty. 76 …”
Section: Treatment Strategies and Outcomesmentioning
confidence: 99%
“…30,41,70,71 However, recent data on the impact of kyphoplasty or vertebroplasty on HRQOL are limited, and vertebroplasty is controversial, as studies on its efficacy in reducing mCIBP are mixed. [72][73][74][75] A 2021 publication reported that, in patients with cancer pain due to bone metastases, pain was significantly reduced and HRQOL was significantly improved up to 6 months after either radiofrequency ablation alone or radiofrequency ablation with vertebroplasty. 76 Surgery is an option for serious complications of bone metastases, including restoration of function because of spinal instability or impending spinal instability and pain that is intractable or was not relieved by nonsurgical therapy.…”
Section: Minimally Invasive and Surgical Interventionsmentioning
confidence: 99%